No woman is illegal: Re-introducing antiracism in feminism - Edthofer, Julia; Gouma, Assimina (The Greek Review of Social Research, 2013)
This is an approach of the issue of anti-racism in relation to feminism taking as example the German speaking countries. We argue that the efforts of some representatives of “feminism” to legitimize structural racism in the name of women’s rights had great acceptance in the public sphere of several European countries. In some cases this situation even created alliances between the far right and feminists. On the other hand, anti-immigrant policies in the name of women’s liberation generated resistance in both social movements and theoretical approaches in the field of anti-racist feminism. Especially self-organizations of migrant women have played a leading role in the political movement against anti-immigrant measures as well in the theoretical approach to anti-racist feminism.